COMMENTS ON PROFESSOR PATON'S PAPER BY S.J. BROAD. - Broad, S. J. (The Accounting Review, 1936)
Abstract Real estate is a simple form of capital; but the same underlying principles of valuation apply to industrial enterprises. As Professor Paton has pointed out, the physical elements of the properties and their intrinsic value are only one, and not the most important, consideration. The cost of replacement value of the properties of an enterprise may be considerable, but the enterprise as a whole possesses value only in proportion to its ability to supply human wants and thus create reasonable and continued profits. Economic factors are no less important. The position of the industry in relation to competing industries and competitive conditions within the industry itself; the possible effect of changes in local taxation or in tariffs, on the costs of raw materials and products; the organization of the industry as to price control and labor relations; any or all of these may have an important bearing on the continued profitableness of the enterprise. Some of the most far-reaching and fundamental conditions relating to an industrial enterprise in our complex modern civilization are human and social in their nature. Every successful business must have a sound reason for its existence and that reason is found ultimately in the satisfaction of human wants.